2014
DOI: 10.3390/ma7053481
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Hydrophobic Phthalocyanine with Poly(N-isopropylacrylamide)/Lipid Composite Microspheres for Thermo-Responsive Release and Photodynamic Therapy

Abstract: Phthalocyanine (Pc) is a type of promising sensitizer molecules for photodynamic therapy (PDT), but its hydrophobicity substantially prevents its applications. In this study, we efficiently encapsulate Pc into poly(N-isopropylacrylamide) (pNIPAM) microgel particles, without or with lipid decoration (i.e., Pc@pNIPAM or Pc@pNIPAM/lipid), to improve its water solubility and prevent aggregation in aqueous medium. The incorporation of lipid molecules significantly enhances the Pc loading efficiency of pNIPAM. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
2
8
0
1
Order By: Relevance
“…The characteristic bands of plain G-1 and G-2 formulations and TA-loaded MPs, previously published, were maintained nearly unchanged in both LG-1 and LG-2 formulations and no new bands were detected, as shown in Figure . , This confirms the absence of any new bonds that could be formed within the MPs–hydrogel formulations, indicating that the interaction between TA-loaded MPs and both G-1 and G-2 hydrogels is most probably hydrophobic in nature. Similar results were previously obtained by Liu et al…”
Section: Results and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The characteristic bands of plain G-1 and G-2 formulations and TA-loaded MPs, previously published, were maintained nearly unchanged in both LG-1 and LG-2 formulations and no new bands were detected, as shown in Figure . , This confirms the absence of any new bonds that could be formed within the MPs–hydrogel formulations, indicating that the interaction between TA-loaded MPs and both G-1 and G-2 hydrogels is most probably hydrophobic in nature. Similar results were previously obtained by Liu et al…”
Section: Results and Discussionsupporting
confidence: 93%
“…17,27 This confirms the absence of any new bonds that could be formed within the MPs−hydrogel formulations, indicating that the interaction between TAloaded MPs and both G-1 and G-2 hydrogels is most probably hydrophobic in nature. Similar results were previously obtained by Liu et al 52 3.4.4. Viscosity Measurements.…”
Section: In Vitro Mass Erosionsupporting
confidence: 92%
“…One reason the solubility enhancement is so beneficial is that the reactions of pterins are not amenable to common organic solvents and purification techniques. In addition to solubility enhancements, it is logical to suggest an increase in the pterins' resistance against forming of aggregates due to alkylation, similar instances of deaggregation of porphyrins and other aromatics due to alkylation in organic solvents (57)(58)(59)(60)(61)(62)(63)(64)(65). This decrease in aggregation has proven necessary to improve sensitizer performance (66)(67)(68).…”
Section: Mechanistic Summarymentioning
confidence: 99%
“…Additionally, Liu et al [ 88 ] reported microgel particles consisting of poly(N-isopropylacrylamide)/lipid (pNIPAM/lipid) composite for thermo-responsive release of PDT agents. Microgel particles have emerged as an interesting system for drug delivery because they combine the unique properties of a gel with those of micro-/nanoparticles.…”
Section: Phthalocyanine-polymeric Nanoparticle Delivery Systems For Cancer Photodynamic Therapymentioning
confidence: 99%